A Systematic Study on Class Characteristics in the Malayalam Script - Vinny Sharma; Anuwanshi Sharma (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: The interrogation of whether a forensic manuscript examiner should provide estimation about composition on handwritten documents in a foreign linguistic has been debated since science’s inception. There is a distinct divide among the discipline’s experts, with some in favor of expressing opinion and the rest𿿿ercely opposed. Aim: The aim of this study describes the class and individual characteristics of Malayalam scripts, laying the groundwork for script forensic testing. Material and Method: When this subject is presented in the context of Indian linguistic diversity, a surveyor who is normally aware with a particular linguistic is challenged with the task of analyzing papers in more than eighteen dialects, all of which is extremely distinct from the others. Fifty samples in the Malayalam language collected for thorough analysis. The handwritten samples were gathered from several writers. The𿿿fty writers knowing the above languages were selected offer the samples in their own linguistic for the assessment.Result: The majority of symbols in the Dravidian scripts are cursive, with the exception of a few straight-line stroked signs. The writers highly endorse the motivation for document experts to examine these foreign scripts and offer a conclusive verdict after thoroughly evaluating the possibilities and constraints by examining documents. Conclusion: After a careful and thorough examination of handwritten samples, when comparing like with like, a document examiner who is unfamiliar with the script must know what each letter or𿿿gure is and where it appears